Cell Non-Autonomous Activation of Flavin-containing Monooxygenase Promotes Longevity and Healthspan - Leiser, Scott F. (Science, 2015)
Stabilization of the hypoxia-inducible factor-1 (HIF-1) increases lifespan and healthspan in nematodes through an unknown mechanism. We report that neuronal stabilization of HIF-1 mediates these effects in C. elegans through a cell non-autonomous signal to the intestine resulting in activation of the xenobiotic detoxification enzyme flavin-containing monooxygenase-2 (FMO-2). This pro-longevity signal requires the serotonin biosynthetic enzyme TPH-1 in neurons and the serotonin receptor SER-7 in the intestine. Intestinal FMO-2 is also activated by dietary restriction (DR) and necessary for DR-mediated lifespan extension, suggesting that this enzyme represents a point of convergence for two distinct longevity pathways. FMOs are conserved in eukaryotes and induced by multiple lifespan-extending interventions in mice, suggesting that these enzymes may play a critical role in promoting health and longevity across phyla.